Male reproductive phenotypes of genetically altered laboratory mice (Mus musculus): a review based on pertinent literature from the last three decades - Buranaamnuay, Kakanang (Frontiers in Veterinary Science, 2024)
Laboratory mice (Mus musculus) are preferred animals for biomedical research due to the close relationship with humans in several aspects. Therefore, mice with diverse genetic traits have been generated to mimic human characteristics of interest. Some genetically altered mouse strains, on purpose or by accident, have reproductive phenotypes and/or fertility deviating from wild-type mice. The distinct reproductive phenotypes of genetically altered male mice mentioned in this paper are grouped based on reproductive organs, beginning with the brain (i.e., the hypothalamus and anterior pituitary) that regulates sexual maturity and development, the testis where male gametes and sex steroid hormones are produced, the epididymis, the accessory sex glands, and the penis which involve in sperm maturation, storage, and ejaculation. Also, distinct characteristics of mature sperm from genetically altered mice are described here. This repository will hopefully be a valuable resource for both humans, in terms of future biomedical research, and mice, in the aspect of the establishment of optimal sperm preservation protocols for individual mouse strains.